2011
DOI: 10.1371/journal.pone.0025835
|View full text |Cite
|
Sign up to set email alerts
|

Major Population Expansion of East Asians Began before Neolithic Time: Evidence of mtDNA Genomes

Abstract: It is a major question in archaeology and anthropology whether human populations started to grow primarily after the advent of agriculture, i.e., the Neolithic time, especially in East Asia, which was one of the centers of ancient agricultural civilization. To answer this question requires an accurate estimation of the time of lineage expansion as well as that of population expansion in a population sample without ascertainment bias. In this study, we analyzed all available mtDNA genomes of East Asians ascerta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
45
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 48 publications
10
45
0
1
Order By: Relevance
“…As expected, from the BSP plot including all European samples in Macrohaplogroup N (Figure 5B), we found that the expansion began ~ 13 kya and showed a continuous trend to nowadays, which is very similar to the result of BSP analysis of East Asian14. The population expansion began ~ 13 kya might correlate to lineages H1, H3, J1c, J1c3, K1, T1, U5a1, V and W.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…As expected, from the BSP plot including all European samples in Macrohaplogroup N (Figure 5B), we found that the expansion began ~ 13 kya and showed a continuous trend to nowadays, which is very similar to the result of BSP analysis of East Asian14. The population expansion began ~ 13 kya might correlate to lineages H1, H3, J1c, J1c3, K1, T1, U5a1, V and W.…”
Section: Resultssupporting
confidence: 86%
“…Φ ST distances between populations in current study or previous analysis14213355565758596061 were calculated in Arlequin 3.11 also via coding regions, and plotted in PAST 1.8562 with a non-metric multidimensional scaling method (see Figure S1), showing that populations in each continent were clustered together.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we detected an earlier expansion before NDT (9-11 kya). This scenario of MTBC lineage 2 is consistent with the latest anthropological findings that suggested the population expansion in East Asia started before the agriculture transition (45). Taken together, our data support a southern origin and a parallel evolution between MTBC lineage 2 and modern humans in East Asia.…”
Section: The Southern East Asia Origin and Parallel Evolution Of Mtbcsupporting
confidence: 90%
“…Population genetic comparison showed that the T allele frequency of rs35356161 in our study cohorts was lower than that in CHB or CHS cohort in the 1,000 Genomes Project. As described, the CHB population was collected in Beijing surrounding areas and the CHS population was recruited in Hunan and Fujian Provinces (37). However, participants of the present study were collected in Yangtze River Delta.…”
Section: Discussionmentioning
confidence: 99%